Effect of accelerated crystallization of silicum and germanium - Червоный, Иван Федорович (Technology audit and production reserves, 2014)
The research results of silicium and germanium crystallization from a melt at an increased rate are given. It was found that during crystallization of monatomic substances as limiting factors it is necessary to consider not only physical factors, i.e. kinetics at the crystallization front along with heat and mass transfer, but also crystallochemical ones, i.e. coordinating atoms and type of interatomic bindings. The possibility of increasing the crystallization rate due to the "tunneling" effect of silicium crystallization, namely at high temperature gradients in the first-order phase transition, an intermittent ("tunnel") transition of silicium density in the liquid phase occurs ranging from 2.53 g/cm3 to 2.33 g/cm3, is set up. The transition is realized by an abtupt change of crystallochemical properties of the groups of atoms from a octahedral coordination to a tetrahedral one. Silicium monocrystals, grown at an increased rate of crystallization have perfect structure and can be used in electronics, biomedicine, power electronics, power electronics technologies and other fields, where crystals with increased structural perfection are applied.